Photoluminescence study of deep donor- deep acceptor pairs in Cu2ZnSnS4. (15th June 2018) - Krustok, J.; Raadik, T.; Grossberg, M.; Kauk-Kuusik, M.; Trifiletti, V.; Binetti, S.
Abstract: We present photoluminescence (PL) studies of high quality Cu2 ZnSnS4 single crystals and thin films. At T = 10 K two PL bands (D1 and D2 ) were detected in both samples at about 1.35 eV and 1.27 eV. The temperature and laser power dependencies indicate that the properties of PL bands can be explained by deep donor-deep acceptor pair model, where the D1 and D2 bands result from a recombination between pairs of the closest neighbors, and between pairs of the next-closest neighbors, respectively. The donor defect in these pairs is suggested to be an interstitial Zn atom and located in either of the two possible interstitial positions. The most probable deep acceptor defect in this pair is CuZn .